Developing a Book for Teaching Reading Skills in the Context of Local Culture: The Department of Arabic Language Teaching at Indonesia University | Tathwir Kitab li-Ta'lim Maharat al-Qira'ah fi Siyaq al-Thaqafah al-Mahalliyyah: Qism Ta'lim al-Lughah al-'Arabiyyah fi Jami'ah Indonesia - Suwandi Suwandi; Sutaman Sutaman; M. Samsul Ulum; Diaya Uddeen Deab Mahmoud Alzitawi; Supangat Supangat (Al-Ta'rib)
Students do not have a specific book for learning maharah qiro’ah and find it difficult to understand qiro’ah texts because the material taught does not align with local wisdom. Therefore, the objectives of this research are: First, to produce an Arabic textbook based on a local wisdom approach. Second, to measure the effectiveness of the Arabic textbook. This research is a type of research and development (R&D) that follows eight of the ten steps proposed by Borg and Gall. The data collection process includes observation, interviews, questionnaires, and documentation. This textbook is effective in improving students' abilities in maharah qiro’ah, as indicated by the scores obtained, which were 63.27 in the first trial (Pre-Test) and increased to 83.69 in the second trial (Post-Test). Additionally, the questionnaires distributed to students and lecturers after using the locally-based teaching materials show that this product is effective and suitable for use in the Arabic language learning process in the Arabic Language Education Program at UIN Raden Fatah Palembang.